Development of Gamification-Based Mobile Learning to Improve Learning Outcomes for Automotive Measurement Tools - Ranu Iskandar; Putri Khoirin Nashiroh; Febrian Arif Budiman (Edu Komputika Journal, 2025)
Inclusive education, a key priority of SDG 4, requires learning innovations that are accessible and engaging for all learners, including students with disabilities. In Indonesian inclusive schools, limited availability of adaptive learning technology remains a major barrier, particularly for students with mild intellectual disabilities who often struggle with practical competencies such as reading precision measuring tools. This study developed and evaluated a gamification-based mobile learning (m-learning) medium on automotive measurement tools (vernier calipers) tailored to the needs of students with mild intellectual disabilities through accessible design elements (preferred colors, readable fonts, simplified sentences, and adapted assessments). Using a Research and Development (R&D) approach with the ADDIE model, the product was validated by one media expert and one material expert, and its effectiveness was examined through a one-group pretest–posttest design with 35 Grade 10 Automotive Engineering students at SMK Palapa Semarang. Expert validation results indicated that the media was very feasible, with scores of 85% (Display Design), 83% (Technical Quality), 88% (Visual Communication), and 90% (Media Attractiveness), while content feasibility was also very feasible, with 82% (Content Completeness), 87% (Content Accuracy), 84% (Presentation Cohesion), and 86% (Language Use). Student learning outcomes improved substantially, with mean scores increasing from 68.29 (pretest) to 88.86 (posttest), yielding a gain of 20.6 points and reduced score variability (SD from 10.43 to 6.31). These findings suggest that gamification-based m-learning designed using assistive technology principles is feasible and can enhance learning outcomes in inclusive vocational education contexts.